1994
DOI: 10.1111/j.1365-2125.1994.tb04358.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of NG‐monomethyl‐L‐arginine on kinin‐induced vasodilation in the human forearm.

Abstract: 1 We compared effects of NG-monomethyl-L-arginine (L-NMMA), an NO synthase inhibitor, on vasodilator responses to intra-arterial infusion of bradykinin and substance P in the human forearm. 2 Bradykinin (100 pmol min-) increased forearm blood flow when infused into the brachial artery of eight healthy male volunteers, from 2.8 ± 0.2 (mean ± s.e. mean) to 9.3 ± 1.0 ml min-1 per 100 ml forearm volume.3 Co-infusion of L-NMMA (2 jmol min-1 and 4 gmol min-') with bradykinin (100 pmol min-') for 6 min produced respe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
39
1

Year Published

1994
1994
2017
2017

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 55 publications
(42 citation statements)
references
References 25 publications
2
39
1
Order By: Relevance
“…5-MTHF normalised NO-mediated vasodilation in patients with Type II diabetes (s) (#p<0.05) others [9,10]. However, whereas decreased responsiveness of the smooth muscle cells to NO and/or enhanced generation of endothelium-derived constricting factors [27,28] might have contributed to the impaired endothelium-dependent NO-mediated vasodilator response, this data suggests a vital defect in endothelium-derived NO bioavailability in patients with Type II diabetes.…”
Section: Discussionmentioning
confidence: 53%
“…5-MTHF normalised NO-mediated vasodilation in patients with Type II diabetes (s) (#p<0.05) others [9,10]. However, whereas decreased responsiveness of the smooth muscle cells to NO and/or enhanced generation of endothelium-derived constricting factors [27,28] might have contributed to the impaired endothelium-dependent NO-mediated vasodilator response, this data suggests a vital defect in endothelium-derived NO bioavailability in patients with Type II diabetes.…”
Section: Discussionmentioning
confidence: 53%
“…This is consistent with data from previous studies demonstrating that NOS inhibition decreases basal FBF and attenuates the FBF response to BK. 11,24 In contrast, coadministration of L-NMMA had no effect on the tPA response to BK when administered either alone or in combination with indomethacin. This finding conflicts with the observations of Newby et al, 25 who reported that coadministration of L-NMMA attenuated the tPA response to another agonist, substance P; however, Tranquille and Emeis 26 observed no effect of N G -nitro-Larginine on BK-stimulated tPA release from rat vasculature.…”
Section: Discussionmentioning
confidence: 84%
“…20,21 A possible explanation could be that both studies did not use the NO clamp technique; that is, L-NMMA was infused, resulting in vasoconstriction, and subsequently BK was infused while basal flow was not restored. Therefore, the attenuated vasodilation by BK in both studies could have been a result of the changed basal contractile state of the vascular smooth muscles, because it is demonstrated that the greater the precontraction of a vessel, the lesser the relaxant response to the vasodilator.…”
Section: Discussionmentioning
confidence: 99%